Stakeholder motivation as a means toward a proactive shared approach to caring for biodiversity: Application on Plateau de Millevaches. (February 2017) - Brédif, Hervé; Simon, Laurent; Valenzisi, Marc
Abstract: Setting up participation-based processes aimed at involving the stakeholders concerned and defining a consensus for collective rules is often recommended as a means of stemming the tide of biodiversity loss. However, this approach assumes application limits and in particular, stakeholders who are prepared to get together and exchange ideas together with clearly identified and circumscribed biodiversity-related problems. Up on the Plateau de Millevaches in the Limousin region (France), years of tension and conflicts over forests have meant that such conditions are in no way present on the ground. In a deteriorated and deadlocked context, another approach has proven necessary to get the stakeholders back around the table and talking again despite their clear differences and diverging perspectives. A research-action programme "co-constructed" with the key actors present on the Plateau de Millevaches has focused on stakeholder motivations in terms of biodiversity and territory. This has pointed up the large degree of convergence in terms of the fundamental aims of these stakeholders: they have been able to leverage this basic agreement to jointly analyse the problems with which they are confronted and envisage positive ways of dealing with them. After presenting the features of the processes deployed, the underlying concepts and the main phases involved, the article will go on to explain how research into stakeholder motivations in terms of biodiversity can be a useful vehicle for change in a local context that has become completely bogged down. It will also suggest that an adequate response to biodiversity loss is not merely bound up with keeping within certain limits and collective rules but with a proactive, co-constructed and shared approach to territorial quality.